Novel morphological and molecular data for Nasitrema spp. (Digenea: Brachycladiidae) in the East Asian finless porpoise (Neophocaena asiaeorientalis sunameri) - Kim, Sunmin; Youn, Heejeong; Lee, Kyunglee; Lee, Hyunjoo; Kim, Min Ju; Kang, Yeseul; Choe, Seongjun; Georgieva, Simona (Frontiers in Marine Science, 2023)
The East Asian finless porpoise, Neophocaena asiaeorientalis sunameri, ranks among the most endangered species with rapidly decreasing population in the Northwest Pacific. Trematode parasites of the genus Nasitrema that inhabit the air sinuses, inner ear, and the central nervous system of cetaceans frequently cause equilibrium dysfunction, disorientation, interference with echolocation, incoordination, and nervous system degeneration. Due to their specific location and associated pathologies, they have been recognized as one of the causes of cetacean strandings. Stranding data provides crucial information on the species’ biology, population health, and on the status of entire marine ecosystem. However, published data on parasite-induced standings that include information on the causative parasite pathogens are scarce. As part of a wider survey on the causes of East Asian finless porpoise strandings along the west coast of Korea, herein, we provide novel morphological and molecular data on two sympatric species of Nasitrema, namely, Nasitrema spathulatum and Nasitrema sunameri based on newly collected specimens from a stranded alive East Asian finless porpoise at the West coast of Korea. Our study adds a new distribution record for important parasite pathogens in cetaceans and provides the first molecular data for the parasite species recovered, which enabled us to re-evaluate the species relationships within the family Brachycladiidae, a group of important parasite pathogens of marine mammals.